Arqueología y tecnologías de información espacial : una perspectiva Ibero-Americana - Maximiano, Alfredo; Cerrillo Cuenca, Enrique (Archaeopress Publishing Ltd, 2015)
This volume contains papers from the First Iberoamerican Conference on Spatial Archaeology held in 2013 at the University of Cantabria, Spain. The subjects include theoretical contexts of spatial archaeology, relationship between archaeological and ethnographical research, micro-site studies and the interpretation of the environment from archaeo-historical contextualisation.